Pengetahuan Pasien tentang Perawatan Luka Dermatitis Kontak pada Pasien Rawat Jalan Berhubungan dengan Kejadian Dermatitis Infeksiosa - Suharno Suharno; Yophi Nugraha (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the relationship between patient knowledge about the treatment of contact dermatitis and the incidence of infectious dermatitis in Class II B Correctional Institutions in the Majalengka Regency in 2022. The research method is an analytical descriptive with a cross-sectional approach. The results showed that 53 patients (46.5%) in Class II B Penitentiary in Majalengka Regency were included in the criteria of having less knowledge, and 61 people (53.5%) had good knowledge. Fifty-one people (44.7%) were exposed to infectious dermatitis, and 63 (55.3%) were unaffected. In conclusion, there is a statistically significant relationship between patient knowledge about wound care in contact dermatitis and the incidence of infectious dermatitis in Class II B Correctional Institutions in the Majalengka Regency in 2022. Keywords: Dermatitis, Penitentiary, Wound Care